2016
DOI: 10.1302/0301-620x.98b10.37610
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following excision of Morton’s interdigital neuroma

Abstract: The patient-reported outcomes after resection of a symptomatic Morton's neuroma are acceptable but may not be as good as earlier studies suggest. Surgery at several sites can be undertaken safely but caution should be exercised when considering revision surgery. Cite this article: Bone Joint J 2016;98-B:1376-81.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…11,32 Nevertheless, other reports did not confirm this hypothesis. 6,9 In this study, 6 patients presented with 2 neuromas in different spaces of the same foot but showed the same favorable outcomes as patients with 1 isolated neuroma, with only more sensory loss without pain observed.…”
Section: Discussionsupporting
confidence: 60%
“…11,32 Nevertheless, other reports did not confirm this hypothesis. 6,9 In this study, 6 patients presented with 2 neuromas in different spaces of the same foot but showed the same favorable outcomes as patients with 1 isolated neuroma, with only more sensory loss without pain observed.…”
Section: Discussionsupporting
confidence: 60%
“…1921 Interestingly, and quite consistently, only about half of the patients report no pain after surgery, whereas approximately 30% are better than preoperatively but with residual pain, and one in ten is worse than before the surgery. 1921 One study showed similar results between neurectomy and neurectomy combined with intramuscular implantation of the nerve stump. 22 The procedure can be performed either through a dorsal or plantar approach, depending on the surgeon’s training and preference.…”
Section: Operative Management: Techniques and Outcomesmentioning
confidence: 94%
“…Revision surgery can be complicated 26,27 and patient outcomes can be even worse compared to those after the primary exploration and neurectomy. 21 The term ‘recurrent neuroma’ is probably misleading. The ongoing pain may be a result of nerve stump irritation (e.g.…”
Section: Operative Management: Techniques and Outcomesmentioning
confidence: 99%
“…[82][83][84][85] Surgical excision yields a good to excellent outcome in more than 70% of reported cases. 86,87 Lateral Femoral Cutaneous Nerve…”
Section: Treatmentmentioning
confidence: 99%